Penta nitrogen coordinated cobalt single atom catalysts with oxygenated carbon black for electrochemical H2O2 production - Zhang, Wenjun; Choi, Jae Won; Kim, Sooyeon; Le, Thao Thi; Nandy, Subhajit; Hwang, Chang-Kyu; Paek, Sae Yane; Byeon, Ayeong; Chae, Keun Hwa; Lee, Seung Yong; Kim, Sang Hoon; Song, Hakhyeon; et al. (Elsevier BV, 2023)
The two-electrons (2e-) oxygen reduction reaction (ORR) offers a sustainable and decentralized alternative to the traditional synthetics for hydrogen peroxide (H2O2) production. Although various Co single atom catalysts (SACs) have been proposed as highly effective 2e- ORR catalysts, there is still room for improvement through fine-tuned coordination environment. Here, a Co-N5-O-C with the combination of highly coordinated Co-N5 moieties and nearby electro-withdrawing epoxides is first time developed to reach the optimal binding energy of *OOH intermediate, resulting in the ultrahigh mass activity of 87.5 A g-1 at 0.75 V vs. RHE. Moreover, a high H2O2 production rate of 11.3 mol g-1 h-1 at 200 mA cm-2 is also obtained by a flow cell device. Such an efficient in-situ generation of H2O2 further enables 100% degradation of the organic methylene blue pollutant within 15 min through the electro-Fenton process. These findings will provide a new direction for on-site H2O2 synthesis and wastewater treatment.